Sustained Condensation Efficiency on 3D Hybrid Surfaces - Ching‐Wen Lo; Yu‐Hsiang Chen; Ming‐Chang Lu (Small Structures)
Condensation plays a crucial role in various applications. While superhydrophobic surfaces have been employed to enhance condensation, their performance significantly deteriorates with increasing subcooling, limiting their practicality. Hybrid surfaces offer a potential solution for improved condensation at high subcooling, but current designs fail to sustain effective condensation as subcooling rises. This study presents a three‐dimensional (3D) hybrid surface integrating short hydrophobic silicon nanowire arrays with hydrophilic microchannels. The formation of bridging droplets across multiple channels is observed, but they are efficiently removed from the 3D hybrid surface. The 3D hybrid surface exhibits sustained, simultaneous dropwise and filmwise condensation under medium to high subcooling conditions. Notably, it maintains a stable heat transfer coefficient across these subcooling conditions without experiencing the typical decline due to flooding observed on conventional surfaces at elevated subcooling temperatures. When compared to a plain hydrophilic surface at high subcooling, the 3D hybrid surface achieved remarkable improvements of 198% in condensation heat flux and 216% in heat transfer coefficient. This 3D hybrid surface represents a significant breakthrough for enhancing condensation in practical systems operating under high subcooling conditions.